Immatures of Phoebemima ensifera Tippmann, 1960 (Cerambycidae, Lamiinae, Hemilophini) - Casari, Sônia A.; Martins, Ubirajara R. (Papéis Avulsos de Zoologia, 2013)
The larva and pupa of Phoebemima ensifera Tippmann, 1960, collected in Samanea tubulosa (Benth.) and Inga sp. (Mimosaceae) are described and illustrated. This is the first species of Hemilophini with described immatures.